Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Statistical Benchmarking of Scalable Photonic Quantum Systems - Tiedau, J.; Engelkemeier, M.; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Letters)

Quantum Correlations beyond Entanglement and Discord - Köhnke, S.; Agudelo, E.; Schünemann, M.; Schlettwein, O.; Vogel, W.; Sperling, Jan; Hage, B. (Physical Review Letters)

Detector-Agnostic Phase-Space Distributions - Sperling, Jan; Phillips, D. S.; Bulmer, J. F. F; Thekkadath, G. S.; Eckstein, A.; Wolterink, T. A. W.; Lugani, J.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; et al. (Physical Review Letters)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides - Zhao, Jie; Ma, Chaoxuan; Rüsing, Michael; Mookherjea, Shayan (Physical Review Letters)
Keywords: General Physics and Astronomy

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Supersymmetric Polarization Anomaly in Photonic Discrete-Time Quantum Walks - Barkhofen, Sonja; Lorz, Lennart; Nitsche, Thomas; Silberhorn, Christine; Schomerus, Henning (Physical Review Letters)

Proposal for Quantum Simulation via All-Optically-Generated Tensor Network States - Dhand, I.; Engelkemeier, M.; Sansoni, L.; Barkhofen, Sonja; Silberhorn, Christine; Plenio, M. B. (Physical Review Letters)

Tomography and Purification of the Temporal-Mode Structure of Quantum Light - Ansari, Vahid; Donohue, John M.; Allgaier, Markus; Sansoni, Linda; Brecht, Benjamin; Roslund, Jonathan; Treps, Nicolas; Harder, Georg; Silberhorn, Christine (Physical Review Letters)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, J.; Silberhorn, C.; Vogel, W. (Physical Review Letters)

Vortex Multistability and Bessel Vortices in Polariton Condensates. - Ma, Xuekai; Schumacher, Stefan (Physical Review Letters)

Quantum-Limited Time-Frequency Estimation through Mode-Selective Photon Measurement - Donohue, J. M.; Ansari, V.; Řeháček, J.; Hradil, Z.; Stoklasa, B.; Paúr, M.; Sánchez-Soto, L. L.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review Letters)

Observation and Uses of Position-Space Bloch Oscillations in an Ultracold Gas - Geiger, Zachary A.; Fujiwara, Kurt M.; Singh, Kevin; Senaratne, Ruwan; Rajagopal, Shankari V.; Lipatov, Mikhail; Shimasaki, Toshihiko; Driben, Rodislav; Konotop, Vladimir V.; Meier, Torsten; Weld, David M. (Physical Review Letters)

Observation and Uses of Position-Space Bloch Oscillations in an Ultracold Gas - Geiger, Zachary A.; Fujiwara, Kurt M.; Singh, Kevin; Senaratne, Ruwan; Rajagopal, Shankari V.; Lipatov, Mikhail; Shimasaki, Toshihiko; Driben, Rodislav; Konotop, Vladimir V.; Meier, Torsten; Weld, David M. (Physical Review Letters)

Separable and Inseparable Quantum Trajectories - Sperling, Jan; Walmsley, I. A. (Physical Review Letters)

Conditional Hybrid Nonclassicality - Agudelo, E.; Sperling, Jan; Costanzo, L. S.; Bellini, M.; Zavatta, A.; Vogel, W. (Physical Review Letters)

Detector-Independent Verification of Quantum Light - Sperling, Jan; Clements, W. R.; Eckstein, A.; Moore, M.; Renema, J. J.; Kolthammer, W. S.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; Walmsley, I. A. (Physical Review Letters)

Gaussian Boson Sampling - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Barkhofen, Sonja; Silberhorn, Christine; Jex, Igor (Physical Review Letters)

Detection and Control of Spin-Orbit Interactions in a GaAs Hole Quantum Point Contact - Srinivasan, A.; Miserev, D. S.; Hudson, K. L.; Klochan, O.; Muraki, K.; Hirayama, Y.; Reuter, Dirk; Wieck, A. D.; Sushkov, O. P.; Hamilton, A. R. (Physical Review Letters)

Picosecond Control of Quantum Dot Laser Emission by Coherent Phonons - Czerniuk, T.; Wigger, D.; Akimov, A. V.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Kuhn, T.; Reiter, D. E.; Bayer, M. (Physical Review Letters)
A picosecond acoustic pulse can be used to control the lasing emission from semiconductor nanostructures by shifting their electronic transitions. When the active medium, here an ensemble of (In,Ga)As quantum dots, is shifted into or out of resonance with the cavity mode, a large enhancement or suppression of the lasing emission can dynamically be achieved. Most interesting, even in the case when gain medium and cavity mode are in resonance, we observe an enhancement of the lasing due to shaking by coherent phonons. In order to understand the interactions of the nonlinearly coupled photon-exciton-phonon subsystems, we develop a semiclassical model and find an excellent agreement between theory and experiment.

Optically Controlled Orbital Angular Momentum Generation in a Polaritonic Quantum Fluid - Luk, S. M. H.; Kwong, N. H.; Lewandowski, P.; Schumacher, Stefan; Binder, R. (Physical Review Letters)

Creation and Manipulation of Stable Dark Solitons and Vortices in Microcavity Polariton Condensates - Ma, Xuekai; Egorov, Oleg A.; Schumacher, Stefan (Physical Review Letters)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Multipartite Entanglement of a Two-Separable State - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, Jan; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, J.; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Talbot Effect for Exciton Polaritons - Gao, T.; Estrecho, E.; Li, G.; Egorov, O. A.; Ma, Xuekai; Winkler, K.; Kamp, M.; Schneider, C.; Höfling, S.; Truscott, A. G.; Ostrovskaya, E. A. (Physical Review Letters)
Keywords: General Physics and Astronomy

Single-Mode Parametric-Down-Conversion States with 50 Photons as a Source for Mesoscopic Quantum Optics - Harder, Georg; Bartley, Tim; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review Letters)

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

Nonclassicality Phase-Space Functions: More Insight with Fewer Detectors - Luis, Alfredo; Sperling, Jan; Vogel, Werner (Physical Review Letters)

Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene - Böhm, Julian; Bellec, Matthieu; Mortessagne, Fabrice; Kuhl, Ulrich; Barkhofen, Sonja; Gehler, Stefan; Stöckmann, Hans-Jürgen; Foulger, Iain; Gnutzmann, Sven; Tanner, Gregor (Physical Review Letters)

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Structural Quantification of Entanglement - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review Letters)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)

Direct Quantitative Electrical Measurement of Many-Body Interactions in Exciton Complexes in InAs Quantum Dots - Labud, P. A.; Ludwig, A.; Wieck, A. D.; Bester, G.; Reuter, Dirk (Physical Review Letters)

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Tomography by Noise - Harder, G.; Mogilevtsev, D.; Korolkova, N.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Driven Quantum Walks - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Silberhorn, Christine; Jex, Igor (Physical Review Letters)
Keywords: General Physics and Astronomy

Multipartite Entanglement Witnesses - Sperling, Jan; Vogel, W. (Physical Review Letters)

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, T.; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)

First Experimental Realization of the Dirac Oscillator - Franco-Villafañe, J. A.; Sadurní, E.; Barkhofen, Sonja; Kuhl, U.; Mortessagne, F.; Seligman, T. H. (Physical Review Letters)

Experimental Observation of a Fundamental Length Scale of Waves in Random Media - Barkhofen, Sonja; Metzger, J. J.; Fleischmann, R.; Kuhl, U.; Stöckmann, H.-J. (Physical Review Letters)

Optical Spectroscopy of Spin Noise - Zapasskii, V. S.; Greilich, A.; Crooker, S. A.; Li, Yan; Kozlov, G. G.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Confinement and Interaction of Single Indirect Excitons in a Voltage-Controlled Trap Formed Inside Double InGaAs Quantum Wells - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review Letters)

Direct Observation of Sub-Binomial Light - Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Physical Review Letters)

Friggeet al.Reply: - Frigge, T.; Wall, S.; Krenzer, B.; Wippermann, St.; Sanna, S.; Klasing, F.; Hanisch-Blicharski, A.; Kammler, M.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review Letters)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Sub-Binomial Light - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review Letters)

Probing Single-Charge Fluctuations at aGaAs/AlAsInterface Using Laser Spectroscopy on a Nearby InGaAs Quantum Dot - Houel, J.; Kuhlmann, A. V.; Greuter, L.; Xue, F.; Poggio, M.; Gerardot, B. D.; Dalgarno, P. A.; Badolato, A.; Petroff, P. M.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; et al. (Physical Review Letters)

Intrinsic Spin Fluctuations Reveal the Dynamical Response Function of Holes Coupled to Nuclear Spin Baths in (In,Ga)As Quantum Dots - Li, Yan; Sinitsyn, N.; Smith, D. L.; Reuter, Dirk; Wieck, A. D.; Yakovlev, D. R.; Bayer, M.; Crooker, S. A. (Physical Review Letters)

Atomistic Picture of Charge Density Wave Formation at Surfaces - Wall, Simone; Krenzer, Boris; Wippermann, Stefan; Sanna, Simone; Klasing, Friedrich; Hanisch-Blicharski, Anja; Kammler, Martin; Schmidt, Wolf Gero; Horn-von Hoegen, Michael (Physical Review Letters)

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Towards the Origin of the Nonlinear Response in Hybrid Plasmonic Systems - Utikal, Tobias; Zentgraf, Thomas; Paul, Thomas; Rockstuhl, Carsten; Lederer, Falk; Lippitz, Markus; Giessen, Harald (Physical Review Letters)

Dynamic Nuclear Spin Resonance inn-GaAs - Chen, Y. S.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Physical Review Letters)

Optical Control of Coherent Interactions between Electron Spins in InGaAs Quantum Dots - Spatzek, S.; Greilich, A.; Economou, Sophia E.; Varwig, S.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review Letters)

Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Photon Propagation in a Discrete Fiber Network: An Interplay of Coherence and Losses - Regensburger, Alois; Bersch, Christoph; Hinrichs, Benjamin; Onishchukov, Georgy; Schreiber, Andreas; Silberhorn, Christine; Peschel, Ulf (Physical Review Letters)
Keywords: General Physics and Astronomy

Decoherence and Disorder in Quantum Walks: From Ballistic Spread to Localization - Schreiber, A.; Cassemiro, K. N.; Potoček, V.; Gábris, A.; Jex, I.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Highly Efficient Single-Pass Source of Pulsed Single-Mode Twin Beams of Light - Eckstein, Andreas; Christ, Andreas; Mosley, Peter J.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Experimental Observation of Quantum Talbot Effects - Song, Xin-Bing; Wang, Hai-Bo; Xiong, Jun; Wang, Kaige; Zhang, Xiangdong; Luo, Kai Hong; Wu, Ling-An (Physical Review Letters)

All Nonclassical Correlations Can Be Activated into Distillable Entanglement - Piani, Marco; Gharibian, Sevag; Adesso, Gerardo; Calsamiglia, John; Horodecki, Paweł; Winter, Andreas (Physical Review Letters)
We devise a protocol in which general nonclassical multipartite correlations produce a physically relevant effect, leading to the creation of bipartite entanglement. In particular, we show that the relative entropy of quantumness, which measures all nonclassical correlations among subsystems of a quantum system, is equivalent to and can be operationally interpreted as the minimum distillable entanglement generated between the system and local ancillae in our protocol. We emphasize the key role of state mixedness in maximizing nonclassicality: Mixed entangled states can be arbitrarily more nonclassical than separable and pure entangled states.

Quantized Magnetic Confinement in Quantum Wires - Tarasov, A.; Hugger, S.; Xu, Hengyi; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Spin Noise of Electrons and Holes in Self-Assembled Quantum Dots - Crooker, S. A.; Brandt, J.; Sandfort, C.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

“Artificial Atoms” in Magnetic Fields: Wave-Function Shaping and Phase-Sensitive Tunneling - Lei, Wen; Notthoff, Christian; Peng, Jie; Reuter, Dirk; Wieck, Andreas; Bester, Gabriel; Lorke, Axel (Physical Review Letters)

Entropy Explains Metal-Insulator Transition of the Si(111)-In Nanowire Array - Wippermann, S.; Schmidt, Wolf Gero (Physical Review Letters)

Probing the Negative Wigner Function of a Pulsed Single Photon Point by Point - Laiho, Kaisa; Cassemiro, Katiúscia N.; Gross, David; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Photons Walking the Line: A Quantum Walk with Adjustable Coin Operations - Schreiber, A.; Cassemiro, K. N.; Potoček, V.; Gábris, A.; Mosley, P. J.; Andersson, E.; Jex, I.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Accessing Higher Order Correlations in Quantum Optical States by Time Multiplexing - Avenhaus, M.; Laiho, K.; Chekhova, M. V.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Reversal of Coherently Controlled Ultrafast Photocurrents by Band Mixing in Undoped GaAs Quantum Wells - Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Physical Review Letters)
It is demonstrated that valence-band mixing in GaAs quantum wells tremendously modifies electronic transport. A coherent control scheme in which ultrafast currents are optically injected into undoped GaAs quantum wells upon excitation with femtosecond laser pulses is employed. An oscillatory dependence of the injection current amplitude and direction on the excitation photon energy is observed. A microscopic theoretical analysis shows that this current reversal is caused by the coupling of the light- and heavy-hole bands and that the hole currents dominate the overall current response. These surprising consequences of band mixing illuminate fundamental physics as they are unique for experiments which are able to monitor electronic transport resulting from carriers with relatively large momenta.
Keywords: tet_topic_qw

Long-Term Hole Spin Memory in the Resonantly Amplified Spin Coherence ofInGaAs/GaAsQuantum Well Electrons - Yugova, I. A.; Sokolova, A. A.; Yakovlev, D. R.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Electron-Spin Beat Susceptibility of Excitons in Semiconductor Quantum Wells - Kwong, N. H.; Schumacher, Stefan; Binder, R. (Physical Review Letters)

Structure of Si(111)-In Nanowires Determined from the Midinfrared Optical Response - Chandola, S.; Hinrichs, K.; Gensch, M.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Fleischer, K.; McGilp, J. F. (Physical Review Letters)

Spin Accumulation and Spin Relaxation in a Large Open Quantum Dot - Koop, E. J.; van Wees, B. J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review Letters)

Resolving the Optical Spectrum of Water: Coordination and Electrostatic Effects - Hermann, A.; Schmidt, Wolf Gero; Schwerdtfeger, P. (Physical Review Letters)

Adatom-Induced Conductance Modification of In Nanowires: Potential-Well Scattering and Structural Effects - Wippermann, S.; Koch, N.; Schmidt, Wolf Gero (Physical Review Letters)

Correlation Effects in Disordered Metallic Photonic Crystal Slabs - Nau, D.; Schönhardt, A.; Bauer, Ch.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Klein, M. W.; Giessen, H. (Physical Review Letters)

Subsecond Spin Relaxation Times in Quantum Dots at Zero Applied Magnetic Field Due to a Strong Electron-Nuclear Interaction - Oulton, R.; Greilich, A.; Verbin, S. Yu.; Cherbunin, R. V.; Auer, T.; Yakovlev, D. R.; Bayer, M.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Aharonov-Bohm Oscillations in the Presence of Strong Spin-Orbit Interactions - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physical Review Letters)

Spin Coherence of Holes inGaAs/(Al,Ga)AsQuantum Wells - Syperek, M.; Yakovlev, D. R.; Greilich, A.; Misiewicz, J.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Detection of Coherent Oceanic Structures via Transfer Operators - Froyland, Gary; Padberg, Kathrin; England, Matthew H.; Treguier, Anne Marie (Physical Review Letters)

Long-Range Chiral Recognition due to Substrate Locking and Substrate-Adsorbate Charge Transfer - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review Letters)

Hexagon versus Trimer Formation in In Nanowires on Si(111): Energetics and Quantum Conductance - Stekolnikov, A. A.; Seino, K.; Bechstedt, F.; Wippermann, S.; Schmidt, Wolf Gero; Calzolari, A.; Nardelli, M. Buongiorno (Physical Review Letters)

Optical Control of Spin Coherence in Singly Charged(In,Ga)As/GaAsQuantum Dots - Greilich, A.; Oulton, R.; Zhukov, E. A.; Yugova, I. A.; Yakovlev, D. R.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review Letters)

Scaling of the Low-Temperature Dephasing Rate in Kondo Systems - Mallet, F.; Ericsson, J.; Mailly, D.; Ünlübayir, S.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Micklitz, T.; Rosch, A.; Costi, T. A.; Saminadayar, L.; Bäuerle, C. (Physical Review Letters)

Structure and Magnetization of Small Monodisperse Platinum Clusters - Liu, Xiong; Bauer, Matthias; Bertagnolli, Helmut; Roduner, Emil; van Slageren, Joris; Phillipp, Fritz (Physical Review Letters)
Keywords: General Physics and Astronomy

Characterization of Disorder in Semiconductors via Single-Photon Interferometry - Bozsoki, P.; Thomas, P.; Kira, M.; Hoyer, W.; Meier, Torsten; Koch, S. W.; Maschke, K.; Varga, I.; Stolz, H. (Physical Review Letters)
The method of angular photonic correlations of spontaneous emission is introduced as an experimental, purely optical scheme to characterize disorder in semiconductor nanostructures. The theoretical expression for the angular correlations is derived and numerically evaluated for a model system. The results demonstrate how the proposed experimental method yields direct information about the spatial distribution of the relevant states and thus on the disorder present in the system.

Coulomb-Interaction-Induced Incomplete Shell Filling in the Hole System of InAs Quantum Dots - Reuter, D.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Wibbelhoff, O.; Meier, Cedrik; Lorke, A.; Maan, J. C. (Physical Review Letters)